DISSEMINATING KNOWLEDGE REGARDING SHARIA-COMPLIANT FAMILY FINANCIAL PLANNING - Indriyarti, Eko Retno; Hermi, Hermi; Wardhani, Nurhastuti Kesumo (Universitas Bunda Mulia, 2025)
Islamic financial planning is crucial for Muslim households to guarantee financial stability and adherence to Sharia standards. Strategic planning facilitates sound financial decision-making, risk management, and the attainment of financial stability. There is a growing demand for financial planning that adheres to Sharia principles among individuals seeking to align their financial management with Islamic beliefs. This aligns with the considerable amount of community service initiatives on this subject conducted in Indonesia. This include activities conducted by the implementing team comprised of lecturers at a university in Jakarta. This activity was conducted in person in mid-December 2024. The approach employed in executing this activity was supplying materials and facilitating question-and-answer discussions. This activity proceeded seamlessly. The assessment of feedback regarding the activity's outcomes was conducted in two phases: pre-test and post-test. The feedback measurement results indicated a knowledge growth, with an average enhancement of 15.89%. The greatest significant enhancement in understanding was in item 2, namely concerning gharar in Islamic finance, which approached 36%. The subsequent most significant rise (exceeding 24%) was on item 5, specifically concerning the primary foundation for decision-making in sharia investment. The subsequent area of knowledge enhancement, nearly attaining 21%, was to item 10, namely concerning the primary priority in the distribution of sharia family income. Such activities must be conducted periodically. By cultivating a culture of learning, sharing, and mutual support, socialization and knowledge dissemination enable families to effectively implement Sharia principles in their financial planning, resulting in enhanced financial well-being and social responsibility.